The Need Analysis of Technology-Based Project-Based Learning in Higher Education - Gede Angga Pratama Anugraha; Ni Nyoman Padmadewi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
21st-century learning places more emphasis on student-centered learning and requires students to develop 6C competencies. In line with this, the project-based learning method can be used as a method that can help students to develop their abilities, especially in language skills subjects. This study aims to analyses the characteristics of technology-based project-based learning needed in teaching language skills in tertiary institutions. This research used an explanatory mixed method. The language skills courses were analyzed in terms of the current and desired conditions in four aspects such as context, input, process, and product. The data were collected using questionnaires, interviews, and document analysis. To provide trustworthiness or validity and reliability, this study used the source triangulation method.The results of the study revealed that the conceptual framework regarding the application of project-based learning through technology in teaching language skills courses should be added to higher education. The existence of a conceptual framework can assist lecturers in implementing project-based learning in the language skills class.